1995
DOI: 10.1111/j.1365-246x.1995.tb06868.x
|View full text |Cite
|
Sign up to set email alerts
|

Linearized inversion of 3-D multi-offset data: background reconstruction and AVO inversion

Abstract: We present a linearized inversion algorithm for 3-D multi-offset seismic reflection data. The fundamental assumptions are that the background medium is only depth-dependent and that the 3-D multi-offset seismic data are regularly sampled as a series of 2-D multi-offset profiles. Our algorithm can be performed in the following three steps.(1) The pressure field P(x, y, h, t ) is 4-D Fourier transformed to P(k,, k,, k,,, o) with respect to the midpoint coordinates (x, y), the half-offset coordinates (h, 0), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Stewart, Zhang and Guthoff () showed that the Lamé parameters (λ and μ) of a medium better differentiate rock properties. The Zoeppritz equations are the basis of the prestack AVO/AVA inversion, but scholars have used numerous approximate equations for inversion because the Zoeppritz equations are strongly nonlinear (Ikelle ; Buland and Omre ; Li et al . ; Yin, Yang and Zhang ).…”
Section: Introductionmentioning
confidence: 99%
“…Stewart, Zhang and Guthoff () showed that the Lamé parameters (λ and μ) of a medium better differentiate rock properties. The Zoeppritz equations are the basis of the prestack AVO/AVA inversion, but scholars have used numerous approximate equations for inversion because the Zoeppritz equations are strongly nonlinear (Ikelle ; Buland and Omre ; Li et al . ; Yin, Yang and Zhang ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, its closed form makes Born approximation very attractive for constructing inversion algorithms (e.g. Snieder 1990; Ikelle 1995de). However, the adaptation of Born‐based solutions to the forward problem of multicomponent OBS data requires (1) the explicit introduction of the boundary conditions at a water/solid interface, (2) the use of the reciprocity theorem for a fluid/solid configuration and (3) the use of P ‐ and S ‐wave potentials.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, the system of integral equations for small perturbations of elastic parameters was deduced and the uniqueness of the inverse problems was proved. Further, the similar approach was applied in [15] for the linearized inverse problem for elastic wave equation in the frequency domain. In [16] it was generalized for anisotropic elastic medium.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that in these papers, maybe except [15,16], the main attention was paid to formal derivation of some mathematical relations which later were used in order to deduce some numerical algorithm of linearized inversion. Unfortunately, influence of such input parameters of the method as size of apertures, noise level, proximity of a priori known background to the exact structure of the medium under consideration and so on onto stability and quality of the gained results happened to be here out of interests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation